AN INTROSPECTIVE ASSESSMENT OF VOLLEYBALL AND CRICKET PLAYERS ON THE BASIS OF THEIR SELF-UNDERSTANDING - Bilal Ahmad Bhat (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2020)
At Insights, we believe self-awareness is the basis for all human endeavours and an essential requirement for sporting excellence. We therefore provide an offering aimed at enhancing individuals’ levels of self-awareness through the lens of Jungian typology, known as Insights Discovery or introspection.The study was intended to explore the level of self-understanding of cricket and volleyball players. 400 cricket and volleyball players were selected by using random sampling technique. All the respondents were selected within the age group of 14-21 years. Self-Understanding Scale (SUS) developed by AktherBanoo&SushmaaTalesera (2014) was uses for data collection. The collected data was subjected to statistical treatment by using Frequency, Percentage, Mean, SD and ‘t’ value. Results revealed that cricket and volleyball players differ significantly on various levels of self-understanding. Cricket players were seen with highly level of self-understanding as compared to Volleyball players. Key Words: Self-understanding, Volleyball players, Cricket player